PENGEMBANGAN MEDIA PEMBELAJARAN POPUP BOOK DALAM MATERI REVOLUSI TEKNOLOG KOMUNIKASI DAN INFORMASI KELAS XII MAN 5 NEGERI BATANGHARI - Al Badruzzaman, M. Farazh (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2024)
This research and development aims to produce learning media products in the form of Popup Books in learning the history of the communication and information technology revolution after Indonesia's independence period in Class XII MAN 5 Batanghari. The development model used adopts the Lee and owen model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation which is abbreviated as ADDIE. The research subjects of class XII students numbered 25 people. In the one to one trial stage (individual) 4 people obtained a percentage value of 70.37% which was classified in the category "Good", at the small group stage ( Medium group) amounted to 8 students obtained a percentage of 76.51% "Very Good", and at the stage of large group test or field test amounted to 25 students obtained a percentage of 85.11% which was classified in the category "Very Good". The results of this study as a whole obtained from the percentage at each stage obtained a percentage value of 77.33% which is classified as "Very Good".